Development of a detection system towards a basophil-microarray for the diagnosis of allergies - Wang, Xiaowei (2014)
Allergic responses are mainly mediated by immunoglobulin E (IgE) and mast cells or basophils expressing the high-affinity IgE receptor FcεRI. Cross-linking of FcεRI and IgE complexes with allergen induces basophil degranulation and release of inflammatory chemical mediators, leading to clinical symptoms. Common allergy diagnostic tests such as ImmunoCAP, focused on the measurement of specific IgE in patients, commonly lead to misdiagnosis. The allergen-specific IgE in patients’ sera might not always lead to FcεRI cross-linking on mast cells or basophils, resulting in no related clinical symptoms, as observed in some food allergies. In order to mimic the allergic response and generate an in vitro diagnostic device to address these issues, a basophil-microarray platform that couples the diversity of a protein array with the biological output of basophilic cells is being developed. This platform allows testing of up to five thousand allergens using a drop of patient’s blood. In this study, the optimisation steps and preliminary results are presented. The platform in development relies upon the use of a humanised rat basophilic leukaemia (RBL) cell line RBL-703/21 and different methods to measure the levels of basophil activation. ß-hexosaminidase assay showed that the human FcεRI expressing RBL-703/21 cell line was able to bind human IgE in the presence of anti-IgE/allergens and led to degranulation. Fibronectin has shown to greatly avoid cell losses during experiments, calcium ionophore A23187 is an unsuitable positive control due to a fast down regulation of VLA-4 and subsequent detachment of cells. The commercial Ca2+ probe (fluo-4, AM) was shown to efficiently measure the intracellular calcium flux upon activation in the micro-well plate, but due to the lack of a detection system, it can not to be used in the microarray. Two reporter plasmids encoding GFP or DsRed with an NFAT promoter region were transfected into RBL-703/21s and optimised. Both reporter systems were able to detect the presence of functional allergen-specific IgE in the sera of patients, and showed the expected bell–shaped dose response curves. Results correlated with those measured by clinical diagnostic methods. The fluorescence system developed using reporter genes does not need further processing, making it an ideal system for the future development of basophil microarray platforms.